Interpersonal Communication Challenges in Online Learning at the Faculty of Social Sciences, Manado State University - Tuerah, Paulus Robert; Korompis, Manuel Estefanus; Kondoy, Erric; Karwur, Hermon Maurits; Rahman, Rahmania (ICHELSS: International Conference on Humanities, Education, Law, and Social Sciences, 2021)
The Covid 19 Pandemic period had an impact on the implementation of online learning at the Faculty of Social Sciences, Manado State University. Interpersonal communication is needed in the context of building an educational civilization in shaping the whole student personality. The challenge today is the loss of interpersonal communication caused by online learning. The purpose of this study is to see the problems about Interpersonal communication in online learning at the Faculty of Social Sciences, Manado State University. The data collection technique was carried out through observing student activities in online learning, direct interviews and documentation. Researchers also performed data reduction, data display and data analysis. The findings and discussions in this study are (1) messages that are not conveyed optimally (2) There are many disturbances that arise in the online learning process such as network availability, noisy atmosphere during online learning (3) Student responses are not optimal, such as seriousness and activeness in participating in online learning. The three findings are discussed in order to find the best solution. The conclusions and suggestions in this study are as follows: (1) Interpersonal communication between lecturers and students is an important element to be maximized (2) Disturbances that arise during the online learning process need to be anticipated with the seriousness of the student. (3) Student responses need to be activated by finding the right solution. Keywords: Challenges, Interpersonal Communication, Online Learning